Elective, Non-Therapeutic Ventilation - Kluge, Eike-Henner W. (Bioethics, 2000)
Browne, Gillett and Tweeddale propose that the use of non-therapeutic elective ventilation (EV) to secure transplantable organs is ethically indefensible. Their argument centres around several propositions: that explicit patient consent for EV is essential, but since it is not included in the consent process for donation from the patient, using it constitutes assault; that inferring consent for EV from the consent to donate itself is ethically and logically indefensible; and that explicit consent from next-of-kin should neither be sought nor honoured in view of the stress EV may cause to staff and families. This article examines their reasoning and suggests that it is fatally flawed. It argues further that in most cases of donation, not using EV may itself be unethical.